PRESERVING COASTAL CULTURAL HERITAGE: THE NEBE FISHING TRADITION IN PULAU PINANG, TAMBELAN DISTRICT, KEPULAUAN RIAU PROVINCE - Dhina Hardianti; Herdio Fernando; Ajahra Fatimah; Nikodemus Niko (Jurnal Sosiologi UPR, 2026)
Pulau Pinang Village represents a coastal community where ancestral cultural practices continue to be maintained in everyday social life. One of the traditions that remains practiced today is Nebe, a traditional fish-catching technique carried out without the use of nets or bait. This practice involves using a wooden stick to locate fish hiding within crevices among rocks or coral in the shallow coastal waters. The persistence of this tradition is significant not only because it relates to the economic activities of local fishermen, but also because it reflects locally embedded knowledge, ecological skills, and social values that have been transmitted across generations. This study employs a qualitative approach using a descriptive method to explore the social and cultural meanings of the Nebe practice within the community of Pulau Pinang Village. Data were collected through field observations, interviews with local residents, and documentation of the practice, particularly during communal activities and village competitions where Nebe is performed collectively. This methodological approach enables a deeper understanding of how the practice is carried out and how community members interpret its significance within their broader social life. The findings indicate that Nebe functions not merely as a traditional fishing technique but also embodies strong social and cultural dimensions. The tradition serves as a symbol of coastal community identity while reflecting a harmonious relationship between humans and the marine environment. Furthermore, the organization of Nebe in the form of competitions or communal events strengthens social interaction, solidarity, and collective belonging among villagers. The practice also plays an important role in transmitting local wisdom—such as cooperation, sportsmanship, honesty, and respect for ancestral heritage—to younger generations. In this sense, Nebe can be understood as an integral component of the cultural system of Pulau Pinang Village, whose continuity continues to be actively preserved by the community.